AB0665 Hypocholesterolemia at Diagnosis Can Predict the Relapse in Patients with Takayasu Arteritis. (9th June 2015) - Fukui, S.; Ichinose, K.; Tsuji, S.; Umeda, M.; Nishino, A.; Nakashima, Y.; Suzuki, T.; Horai, Y.; Koga, T.; Kawashiri, S.; Iwamoto, N.; Hirai, Y.; et al.
Abstract : Background: Takayasu arteritis (TA) is a rare large vessel vasculitis which predominantly affects young women and often experiences the relapse even after the remission is once introduced. Predicting factors toward the relapse of TA are not well known, however, the co-exsistence of metabolic syndrome is reported to associate with the relapse in patients with ANCA associated vasculitis 1 . Objectives: The aim of this study is to identify the variables at diagnosis to predict the relapse in patients with TA including inflammatory markers, HLA-B52 and metabolic indices. Methods: We retrospectively analyzed 25 patients with TA in Nagasaki University Hospital from April in 2003 to March in 2014. They were all newly diagnosed patients with TA who could be followed up at least 6 months at our hospital. Patients gave their informed consent to be subjected to the protocol, which was approved by the Institutional Review Board of Nagasaki University. We have colletced the baseline variables including clinical symptoms and signs, laboratory data and HLA-B52 by medical records and tried to investigate the associations of these indices with the subsequent relapse. The relapse was judged by Japan College of Rhematology-certified rheumatologists by confirmation of the recurrence with active disease as previously described 2 . Results: The patients were one male and 24 female (96%). The median age at onset was 37.1 years old and that of follow-up duration was 6.1 years. HLA-B52 was found in 11 patients (44%). The relapse was noted in 11 patients (44%). Several indices including fever (>38°), general fatigue, high erythrocyte sedimentation rate (ESR) [median, 57.3 mm/hr (non-relaspe) vs. 89.7 mm/hr (relapse)] and low total cholesterol (Tcho) [median, 192mg/dL (non-relapse) vs. 142 mg/dL (relapse)] were preferentially distributed in the relapse group as compared with non-relapse group. Multivariate analysis in conjunction with the Kaplan-Meier method have found that hypocholesterolemia (<150 mg/dL) at diagnosis is the only predictor toward the subsequent relapse (Odds ratio: 11.6, 95%CI: 1.03-131, non-relapse survival curve is shown in Fig. 1 ). Conclusions: We have found for the first time that hypocholesterolemia at diagnosis is a predictor of the subsequent relapse in patients with TA. Our findings may also show the importance of lipid profiles in consideration of the outcome of vasculitis syndrome. References: Petermann Smits DR, Wilde B, Kianersi Adegani M, et al. Metabolic syndrome in ANCA-associated vasculitis. Rheumatology (Oxford) 2013;52:197-203. Dagna L, Salvo F, Tiraboschi M, et al. Pentraxin-3 as a Marker of Disease Activity in Takayasu Arteritis. Ann Intern Med 2011;155:425-33. Disclosure of Interest: None declared